Avaliação da atividade citotóxica e antibacteriana de um composto triazenido complexado com íon ouro (I) - Nunes, Melise Silveira (2015)
Cancer represents one of the leading causes of death worldwide and efforts to discover more effective anticancer therapies have led to the synthesis of a wide diversity of molecular species. Another major challenge is the anti-infective treatment, because despite the large arsenal of active substances available, many show inefficiency due to the rapid emergence of resistant bacterial strains. As a result, arises the necessity of finding new active substances, more effective and targeted properties in both treatments of neoplasms as microbial resistance. Notably, the Triazenes compounds (TZCs) have been asserting itself as a promising class of metallodrugs with relevant antimicrobial and antiproliferative activity. Moreover, the association of pharmacophoric radical TZC with metal ions, such as gold, leads to a significant increase in biological activity. Because of this wide pharmacological versatility, this study aimed the evaluating in vitro of the biological activity of a compound TZC complexed with ion gold (I). The antibacterial activity was carried out by the conventional method of broth microdilution, through the technique of the minimum inhibitory concentration (MIC), against bacterial strains reference standard American Type Culture Collection (ATCC), clinical isolates with multidrug resistance (MDR) and clinical isolates biofilm producers. Cytotoxicity was evaluated by colorimetric assay based on the reduction of bromide of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide) (MTT) against the standard cell line K562 (Chronic Myeloid Leukemia). The results obtained demonstrate that the compound in study present a narrow spectrum of action, being active only against microorganisms classified as Gram positive, moreover, proved to be active against all isolates producing biofilm when compared to non-producing strains of biofilm. Also showed remarkable cytotoxic activity, with IC50 4.96 μM. Thus, these results demonstrate an alternative to the design of a new class of antibacterial and antitumor metallodrugs with activity.